Huge ventral cervicomedullary neurenteric cyst: A rare entity with good surgical outcome and appraisal - Haque, Moududul; Rahman, Asifur; Ahmed, Nazmin; Alam, Shamsul (Asian Journal of Neurosurgery, 2020)
Neurenteric cysts are rare congenital lesions of benign nature that can be encountered at any level of the neuraxis, starting from the cranium down to coccyx. Rewarding outcome can be achieved with early diagnosis and complete removal of these benign lesions. Here, we report a case of a huge neurenteric cyst in an 11-year-old boy at the ventral craniocervical junction, a rarely reported entity with literature review. In this article, we focus on the clinical presentation, pathogenesis, radiological findings, surgery, and surgical outcome of this benign lesion, as we succeeded to have gratifying result following surgery in our instance.
Keywords: Cervicomedullary; magnetic resonance imaging; neurenteric cysts